2000
DOI: 10.1001/archfami.9.10.1124
|View full text |Cite
|
Sign up to set email alerts
|

Rofecoxib, a New Cyclooxygenase 2 Inhibitor, Shows Sustained Efficacy, Comparable With Other Nonsteroidal Anti-inflammatory Drugs: A 6-Week and a 1-Year Trial in Patients With Osteoarthritis

Abstract: Rofecoxib is effective in treating OA with once-daily dosing for 6 weeks and 1 year. Rofecoxib was generally safe and well-tolerated in OA patients for 6 weeks and 1 year. Arch Fam Med. 2000;9:1124-1134

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 13 publications
2
47
1
4
Order By: Relevance
“…One possible explanation for this observation could be the unrestricted use of up to 4,000 mg acetaminophen daily. Of note, the baseline WOMAC pain subscale scores (often the best predictor of a change) in this study were similar to those reported in other studies (26,27). The secondary efficacy measures (i.e., WOMAC subscale scores, rescue medication usage) supported the primary outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One possible explanation for this observation could be the unrestricted use of up to 4,000 mg acetaminophen daily. Of note, the baseline WOMAC pain subscale scores (often the best predictor of a change) in this study were similar to those reported in other studies (26,27). The secondary efficacy measures (i.e., WOMAC subscale scores, rescue medication usage) supported the primary outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, these doses of AZD3582 were noninferior to rofecoxib 25 mg/day. The change in the WOMAC pain subscale score for placebo from baseline to the average of weeks 4 and 6 was larger in this study (LS mean decrease of 25 mm) than that inferred from other OA studies published recently (26,27). One possible explanation for this observation could be the unrestricted use of up to 4,000 mg acetaminophen daily.…”
Section: Discussioncontrasting
confidence: 68%
“…Doses of 12.5 and 25 mg of rofecoxib were found to provide optimal efficacy during 6 weeks of treatment (Ehrich et al, 1997 and to be more effective than placebo (Truitt et al, 1999;Day et al, 2000;Saag et al, 2000). In phase III clinical trials, treatment with rofecoxib (12.5 or 25 mg/ day) for 1 year was as effective as treatment with ibuprofen (800 mg t.i.d) or diclofenac (50 mg t.i.d.)…”
Section: A Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…In phase III clinical trials, treatment with rofecoxib (12.5 or 25 mg/ day) for 1 year was as effective as treatment with ibuprofen (800 mg t.i.d) or diclofenac (50 mg t.i.d.) (Cannon et al, 2000;Saag et al, 2000).…”
Section: A Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…We identified 11 trials reporting dyspeptic symptoms in patients receiving coxibs versus NSAID NS (10,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). A previous meta-analysis of these trials calculated a pooled risk reduction of 23% for coxibs versus NSAID NS (12).…”
mentioning
confidence: 99%